2022
DOI: 10.1053/j.gastro.2021.05.030
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination and Inflammatory Bowel Disease: Desired Antibody Responses, Future Directions, and a Note of Caution

Abstract: blood-based transcriptomic signature might further improve the LNM predictive efficacy of our risk-assessment model in future studies.Second, the authors suggested that in addition to receiver operating characteristic curve analysis, inclusion of calibration curves that reflect the agreement between the actual and predicted probabilities might be useful. In such analysis, a perfect calibration would be where the observed versus predicted probability would be equal. Once again, we appreciate this suggestion ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Thus, 21 studies were included in their entirety as shown in Table 1. These included 11 prospective studies, seven retrospective studies and three survey‐based studies 16–21,27–41 . The PRISMA Flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 21 studies were included in their entirety as shown in Table 1. These included 11 prospective studies, seven retrospective studies and three survey‐based studies 16–21,27–41 . The PRISMA Flow chart is shown in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…These included 11 prospective studies, seven retrospective studies and three survey‐based studies. 16 , 17 , 18 , 19 , 20 , 21 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 The PRISMA Flow chart is shown in Figure 1 . The study details are shown in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The details of the included studies are illustrated in Table 1 [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] . The details of the excluded studies with the reason for exclusion is shown in Supplementary Table 2 [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] .
Figure 1 PRISMA flow chart depicting the study screening and selection of the systematic review
…”
Section: Resultsmentioning
confidence: 99%
“…After the identi cation and the screening, 147 articles were selected as potential studies. After reading the full text of these articles, 15 articles formed the nal sample and considered for the nal data extraction (10,14,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Inter-rater agreement following the rst round of screening between the investigators was 85% (Cohen's k=0.67).…”
Section: Resultsmentioning
confidence: 99%